Wood Density Variations of Tropical Wood Species: Implications to the Physical Properties of Sawdust as Substrate for Mushroom Cultivation - Maharani Rizki; Yutaka Tamai; Keiichi Koda; Yasuo Kojima; Minoru Terazawa (Wood Research Journal, 2010)
The physical properties of sawdust including particle size distribution, particle density, porosity and water retention of tropical wood species were examined taking sixteen different wood densities users into consideration. Sawdust of each wood species was prepared using a milling machine (type CE TUV, made in Germany) with thickness of band saw size of 2 mm. Particle size of sawdust was classified into 3 classes; Over Size (OS) < 24 mesh (<710 µm); Coarse Particle Size (CPS = 350µm~710 µm) and Fine Particle Size (FPS = 177 µm~250 µm). In relation to the physical properties analysis, OS particle was excluded due to high variation in the particle size distribution but significant lowest in the proportion comparing to the FPS and CPS. Although statistical analysis showed that different wood density revealed relatively weak relationship with particle size distribution however wood density had positively correlated with the particle density. High of wood density tended to make higher particle density of sawdust. In addition, comparison between CPS and FPS for each wood species generally showed that CPS was significantly higher in porosity but lower in particle density and water retention than that FPS. Further, a comparison between different wood species in porosity and water retention showed different pattern, increasing wood density was negatively correlated with the porosity in CPS and also FPS; however the different wood density not showed significant relationship with the water retention.